2000
DOI: 10.1016/s1097-2765(05)00018-3
|View full text |Cite
|
Sign up to set email alerts
|

Pathway Specificity by the Bifunctional Receptor Frizzled Is Determined by Affinity for Wingless

Abstract: The Frizzled (Fz) protein in Drosophila is a bifunctional receptor that acts through a GTPase pathway in planar polarity signaling and as a receptor for Wingless (Wg) using the canonical Wnt pathway. We found that the ligand-binding domain (CRD) of Fz has an approximately 10-fold lower affinity for Wg than the CRD of DFz2, a Wg receptor without polarity activity. When the Fz CRD is replaced by the high-affinity CRD of DFz2, the resulting chimeric protein gains Wg signaling activity, yet also retains polarity s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(76 citation statements)
references
References 48 publications
5
70
1
Order By: Relevance
“…7A-A′′). The apparent difference between our observations and the previous work (Rulifson et al, 2000) most probably reflects a difference in the sensitivity of detection methods rather than in the affinity of two versions of Fz for Wg. Overexpression of Fz2, however, leads to increased Wg levels in the central zone of the P compartment (Fig.…”
Section: Fig 3 Notum Suppresses Wg Signaling Mainly Through Dally contrasting
confidence: 99%
See 2 more Smart Citations
“…7A-A′′). The apparent difference between our observations and the previous work (Rulifson et al, 2000) most probably reflects a difference in the sensitivity of detection methods rather than in the affinity of two versions of Fz for Wg. Overexpression of Fz2, however, leads to increased Wg levels in the central zone of the P compartment (Fig.…”
Section: Fig 3 Notum Suppresses Wg Signaling Mainly Through Dally contrasting
confidence: 99%
“…Previous studies have shown that overexpression of Fz-GPI has no effect on the Wg gradient when examined by conventional staining (Rulifson et al, 2000). However, we found that the extracellular Wg levels are enhanced, and the Wg gradient becomes broader and flatter in the P compartment when overexpressing wild-type Fz (Fig.…”
Section: Fig 3 Notum Suppresses Wg Signaling Mainly Through Dally supporting
confidence: 48%
See 1 more Smart Citation
“…There have been reports that Wnt ligands bind to multiple FZD receptors and vice versa [48,49]. In particular, Wnt5a and Wnt11 also activate the non-canonical Wnt signaling upon binding to FZD7 [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…With the fledgling wingless (wg, Wnt)-dsh (DVL)-zeste white3 (zw3, GSK3) -armadillo (arm, b-catenin) signaling pathway important for embryonic patterning and wing development (Klingensmith and Nusse 1994;Krasnow et al 1995), came along the identification of the second fly Frizzled gene Dfz2 and the finding that Wg is a ligand for Dfz2 and Fz (Bhanot et al 1996). fz(also called Dfz1) and Dfz2 have redundant functions, although Dfz2 has a more prominent role, in Wg signaling, whereas fz/ Dfz1 has a unique role in the PCP pathway (Kennerdell and Carthew 1998;Chen and Struhl 1999;Boutros et al 2000;Rulifson et al 2000).…”
Section: Wnt -Receptor Interactions: Outside the Cell Fzd Receptorsmentioning
confidence: 99%